2014
DOI: 10.2147/oaap.s68858
|View full text |Cite
|
Sign up to set email alerts
|

Follicle growth, ovulation rate, body weight change, and antioxidant and metabolic status in three fat-tailed sheep breeds fed a half-maintenance diet

Abstract: This study aimed to determine the impact of feeding a half-maintenance diet on ovulation rate, metabolic status, and antioxidant status of three native breeds of fat-tailed sheep under Egyptian conditions. Estrus was synchronized with two doses of cloprostenol 11 days apart. The number of preovulatory follicles and corpora lutea were evaluated by transrectal ultrasound. Total antioxidant capacity, superoxide dismutase (SOD), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), total cholesterol, insulin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…There are several metabolic signals that the hypothalamus translates to decode the nutritional status of the animal, to allow or to block the induced release of GnRH by kisspeptin, such as the variations of blood concentrations of insulin and leptin. Starvation and food restriction cause the decrease of blood concentrations of these hormones and disrupt the secretion of gonadotropins in ewes (Viñoles et al, 2005;Abo El-Maaty & Abd El-Gawad, 2014). These hormones are known to regulate kisspeptin neurons by a direct stimulation, or by suppressing the production of orexigenic (appetite-stimulating) neuropeptides, such as the neuropeptide Y (Daniel et al, 2013;De Bond & Smith, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several metabolic signals that the hypothalamus translates to decode the nutritional status of the animal, to allow or to block the induced release of GnRH by kisspeptin, such as the variations of blood concentrations of insulin and leptin. Starvation and food restriction cause the decrease of blood concentrations of these hormones and disrupt the secretion of gonadotropins in ewes (Viñoles et al, 2005;Abo El-Maaty & Abd El-Gawad, 2014). These hormones are known to regulate kisspeptin neurons by a direct stimulation, or by suppressing the production of orexigenic (appetite-stimulating) neuropeptides, such as the neuropeptide Y (Daniel et al, 2013;De Bond & Smith, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present study indicate that the reproductive system of previously undernourished ewes is very sensitive to positive nutritional inputs, which is evidenced by a similar ovulation rate observed between groups of well-nourished ewes. In addition to previous nutritional status, it has been reported that the effect of nutritional input depends on the breed of ewes, since the feeding of ewes with 50% of maintenance ratio for up to 30 days did not affect ovulation rate homogeneously among three different ewe breeds, which might be explained by body fat reserve mobilization to cope undernutrition in fat tail ewes (Abo El-Maaty & Abd El-Gawad, 2014). A similar conclusion can by drawn from the present study because ovulation rate of wellnourished ewes was not affected by a short exposure to a low feeding regimen.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have analyzed the follicular fluid of animals (cattle, mice, sheep, goats, and camels). [37][38][39] One study on human material concluded that there was no statistically significant difference in the concentrations of AST and ALT between the follicular fluid obtained from the follicles from the left and right ovaries. The median AST was 28.5 IU/L, while the average ALT was 13.1 IU/L.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress occurs as a result of an imbalance between ROS and antioxidants. A study conducted in sheep reported that there is a negative correlation between increasing oxidative stress index and ovulation rate (Abo El‐Maaty & Abd El‐Gawad, 2014). Similarly, it is stated that there is a negative correlation between the increase in the oxidative stress index and the fertilization rate in in vivo embryo production in cattle.…”
Section: Discussionmentioning
confidence: 99%